PD-TAP: AN OBJECTIVE AND AUTOMATED MEASURE OF PARKINSON'S DISEASE SEVERITY. Issue 12 (15th November 2016) - Dominey, Thea; Newman, Craig; Carroll, Camille; Noad, Rupert; Appleyard, Benjamin; Deeprose, Catherine; Hall, Stephen
Abstract : The current gold standard for assessment and monitoring of Parkinson's disease (PD) is the unified PD rating scale (UPDRS). While a useful evaluation tool, its application for research is limited by the need for an experienced rater, intra and inter-rater reliability and a 5-point scale. The UPDRS is time-consuming with the specific motor assessment taking >15 minutes to administer. Rapid, objective tools are needed to aid monitoring of PD for research utility. A finger-tapping app (PD-Tap), developed for use on an iPod Touch, was used to test finger tapping performance in 16 patients with idiopathic Parkinson's disease (mean age 66 years and disease duration 12 months) and 16 age-matched-controls (AMC). A fast finger-tapping task taking <1 minute to complete, was found to distinguish PD patients from AMC (t(30)=2.27, p=0.03). Moreover, PD-Tap scores showed high correlation with UPDRS motor scores (r=.69, p=.003). These results support the use of the tool in a research setting. PD-Tap is quick to administer, meaning there is potential to provide a more sensitive indicator of motor function than a 15 minute UPDRS assessment. The app-based nature of the tool is practical, and reproducible in a research environment. Future research aims to define the sensitivity of PD-Tap to evaluate motor fluctuations.